Genome Sequences of Bacteriophages UPEC01, UPEC03, UPEC06, and UPEC07 Infecting Avian Pathogenic Escherichia coli - Kazibwe, George; Ndekezi, Christian; Alinaitwe, Ruth; Alafi, Stephen; Nanteza, Ann; Kimuda, Magambo Phillip; Nakavuma, Jesca Lukanga (Microbiology Resource Announcements, 2022)
Here, we present the genome sequences of four bacteriophages that infect avian pathogenic Escherichia coli. The phages were isolated from raw sewage in Kampala, Uganda. The genome sizes of the phages ranged between 143,140 bp and 178,307 bp, with an average G+C content of 41.25%.
Keywords: Avian Pathogenic Escherichia coli; Genome; Bacteriophages